Enzymatic hydrolysis of lupin protein isolates—Changes in the molecular weight distribution, technofunctional characteristics, and sensory attributes. Issue 8 (25th July 2019) - Schlegel, Katharina; Sontheimer, Katharina; Hickisch, Andrea; Wani, Ali Abas; Eisner, Peter; Schweiggert‐Weisz, Ute
Abstract: Enzymatic hydrolysis of lupin protein isolates (LPI; Lupinus angustifolius L.) was performed with nine different protease preparations to investigate their effect on technofunctionality, sensory properties, and the integrity of the proteins to estimate the reduction of the immunoreactivity. Alcalase 2.4 L, papain, and pepsin were most effective in the degradation of the α‐ and β‐conglutin examined by SDS–PAGE analysis, although the degree of hydrolysis only slightly increased. The technofunctional properties of LPI—solubility, emulsifying, and foaming activity—were improved by most of the proteolytic enzymes with the most impressive increase from 980% foam activity for LPI up to 3, 614% foam activity for pepsin hydrolysate. The formation of bitterness, most likely linked to generation of bitter peptides, was pronounced in the Alcalase hydrolysate, while the other hydrolysates did not show an extensive increase in bitterness compared to the LPI. Other sensory attributes of the hydrolysates—with the exception of Alcalase treatment—were also very similar to the LPI. The results of this study show the potential of enzymatic degradation of LPI to modify the IgE‐reacting polypeptides and to improve the technofunctionality of the isolates and therefore their use as food ingredients. Abstract : The study showed that enzymatic hydrolysis is a useful process for the degradation of lupin allergens. The formation of bitter peptides could be prevented by the utilization of an appropriate enzyme preparation. The technofunctional properties, which are extremely important for a food ingredient, were improved by most of the protease preparations.